Palaeontology of invertebrates - Enay, Raymond (Springer, 1993)
How could life have started on Earth and how did it proceed? After a short discussion of the origin of life on Earth and the origin of the major body plans the invertebrates are presented in the order of increasing complexity by the most significant fossil representatives. In each case, the adaptive significance of the respective forms and/or structure which more or less profoundly changed the original body plan has been treated in detail. In the closing chapter, some general aspects about invertebrates in evolution and palaeoecology, paleobiogeography and biochronology are outlined.